Preparation method and application of hard carbon negative electrode material for sodium ion battery

Agricultural solid waste powder and oxidized asphalt are modified by high-temperature carbonization coating, combined with wheel grinding, ultrasonic vibration screening, ashing of boron-containing alkali metal compounds and acidification modification with dilute hydrochloric acid, and finally sodium ions are obtained through freeze-drying The battery hard carbon negative electrode material solves the problems of serious environmental pollution, high cost and poor material performance of the preparation method in the existing technology, realizes the preparation of efficient and low-cost sodium ion battery negative electrode material, and improves the electrochemical performance of the material.

CN116654897BActive Publication Date: 2025-01-24INNER MONGOLIA SANXIN IND
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310704643.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-14
Publication Date
2025-01-24
Estimated Expiration
2043-06-14

AI Technical Summary

Technical Problem

The existing preparation methods for hard carbon anode materials of sodium ion batteries have problems such as serious environmental pollution, high cost, and poor material performance, which are difficult to meet the high energy density and good cycle performance requirements of sodium ion batteries.

Method used

Agricultural solid waste powder and oxidized asphalt are used for high-temperature carbonization coating modification, combined with wheel grinding and ultrasonic vibration screening, followed by ashing treatment with boron-containing alkali metal compounds, and acidification modification with dilute hydrochloric acid, and finally pass Freeze-drying to obtain hard carbon negative electrode materials for sodium ion batteries.

Benefits of technology

The low-cost and efficient preparation of hard carbon negative electrode materials for sodium-ion batteries has been achieved, reducing the specific surface area of ​​the material, improving first-time efficiency and rate performance, and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116654897B_ABST
    Figure CN116654897B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a preparation method and application of a hard carbon negative electrode material for sodium ion batteries. First, agricultural solid waste powder and oxidized asphalt are evenly mixed and then carbonized at high temperature, then crushed by wheel milling, and sieved by ultrasonic vibration screen; then a substance containing a boron-containing alkali metal compound is added for ashing, and dilute hydrochloric acid is added to the ashing product as a modifier for reaction, and then washed, filtered, and dried to obtain the final product. Adding oxidized asphalt during high-temperature carbonization can improve the initial efficiency, and using wheel milling for crushing has little damage to the structure of the hard carbon negative electrode. The carbonized material is ashed with a boron-containing alkali metal compound and then treated with dilute hydrochloric acid. The addition of the boron-containing alkali metal compound can not only reduce the ash content in the hard carbon negative electrode but also improve its rate performance. The above technical means are used to prepare a sodium ion battery hard carbon negative electrode material with good electrical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a preparation method and application of a hard carbon negative electrode material for a sodium ion battery. Background Art

[0002] New energy vehicles, power storage, and clean energy storage industries are developing rapidly. At present, new energy vehicles and energy storage devices are mainly based on lithium-ion batteries. The rapid development and large-scale application of both have caused the demand and cost of lithium, the raw material of lithium-ion batteries, to rise sharply, and will soon be unable to meet the huge demand for lithium-ion batteries. However, my country's lithium resource reserves are limited, and the demand for lithium-ion batteries can only be met through imports.

[0003] Compared with lithium, the abundance of sodium in the earth's crust is more than 420 times that of lithium, and my country has abundant sodium reserves and does not need to rely on foreign imports. Therefore, sodium-ion batteries have become the only choice to replace lithium-ion batteries.

[0004] Graphite is the most widely used and most technologically mature negative electrode material in lithium-ion batteries today. However, since the radius of sodium ions is larger than that of lithium ions, sodium ions will expand greatly after being embedded in graphite, resulting in extremely poor battery energy density and cycle performance. Therefore, it is urgent to research and develop negative electrode materials specifically for sodium-ion batteries.

[0005] Negative electrode materials with low voltage and high specific capacity characteristics are the key to improving the energy density of sodium-ion batteries. Currently, the development of negative electrode materials with such characteristics is mainly concentrated on hard carbon, soft carbon, tin-based materials, etc. Among these materials, hard carbon materials with a low voltage platform are considered to be the sodium-ion battery negative electrode materials closest to practical applications.

[0006] There are two main methods for preparing hard carbon negative electrode materials for existing sodium ion batteries: 1. Pyrolyze organic resin under high temperature conditions; modify it by liquid phase coating after pyrolysis, and the solvent used for liquid phase coating is also an organic solvent. 2. Pyrolyze petroleum asphalt under high temperature conditions; oxidize and modify petroleum asphalt using concentrated sulfuric acid or hydrogen peroxide. The above technologies all have the following problems: 1) The reaction conditions are harsh, and a large amount of organic volatiles will be produced during the high-temperature treatment of the raw materials, which will cause serious environmental pollution and great cost pressure in terms of environmental protection. 2) The preparation process of polymer materials is complicated and the cost of raw materials is high. 3) The prepared hard carbon negative electrode materials for sodium ion batteries have defects such as large specific surface area, low tapping, low first efficiency, high ash content, and poor rate performance. Summary of the invention

[0007] The purpose of the present invention is to solve the technical defects of the existing sodium ion battery hard carbon negative electrode material production raw materials with strong pollution and high cost, and ultimately prepare a sodium ion battery hard carbon negative electrode material with better electrical properties.

[0008] In order to achieve the above object, the present invention adopts the following technical scheme:

[0009] A method for preparing a hard carbon negative electrode material for a sodium ion battery mainly comprises the following steps:

[0010] (1) mixing agricultural solid waste powder and oxidized asphalt uniformly and then performing high-temperature carbonization coating modification to obtain a modified product, wherein the amount of the oxidized asphalt accounts for 10%-20% of the mass of the agricultural solid waste powder, and the high-temperature carbonization is carried out in a protective gas tube furnace, the carbonization temperature is 800-1000° C., and the carbonization time is 1-5 hours (preferably carbonized at 850-900° C. for 2 hours);

[0011] (2) crushing the modified product obtained in step (1) in a wheel mill, sieving and grading it in an ultrasonic vibration screen, and taking the undersize;

[0012] (3) After the above-mentioned sieve underfill is uniformly mixed with substance A containing a boron-containing alkali metal compound (preferably, the mass ratio of the sieve underfill to substance A is 1:(3-6)), ashing is performed under protective gas conditions at 900-1000° C. for 1-3 hours to obtain an ashing product (preferably ashing at 900° C. for 2 hours), and dilute hydrochloric acid with a concentration of 50-150 ml / L is added to the ashing product as a modifier for reaction, and then washed, filtered, and dried to obtain the final product, a sodium ion battery hard carbon negative electrode material, wherein the mass ratio of the sieve underfill to substance A is 1:(2-4);

[0013] Furthermore, the particle size control conditions of the agricultural solid waste powder in step (1) are as follows:

[0014] D10 = 4-6 μm, D50 = 12-14 μm, D90 < 30 μm, particle size distribution K value = 1.6-2.0;

[0015] Furthermore, in the step (1), the agricultural solid waste powder is obtained by washing, drying, cutting, crushing and sieving agricultural solid waste, wherein the crushing is carried out in a pulverizer, the main engine speed is 12000r / min, the crushing time is 30s-60s; the sieving time is 5-10 minutes, and the sieve hole diameter is 250-325 mesh.

[0016] Furthermore, the agricultural solid waste is potato straw, corn straw and / or sunflower straw.

[0017] Furthermore, the substance A is a boron-containing alkali metal compound or a mixture of a boron-containing alkali metal compound and an alkali metal compound. Furthermore, the substance A is borax or a mixture of sodium carbonate and borax in a mass ratio of 2:8 to 4:6.

[0018] Furthermore, the conditions for the crushing in step (2) are: screw speed 8-25 r / min; grinding time 8-10 minutes; screening conditions are: ultrasonic intensity 20%-80%, amplitude 1-3 mm, screening time 6-10 minutes;

[0019] Furthermore, in step (3), the ratio of the sieve material to the dilute hydrochloric acid is 1 mg: (10-30) mL, preferably 1 mg: (15-20) mL.

[0020] Furthermore, in step (3), ultrapure deionized water is used for washing, the ion conductivity of the ultrapure deionized water is controlled at 1-1.5 μΩ / cm, and the washing is controlled until the pH of the filtrate is greater than 6;

[0021] Furthermore, the drying in step (3) is carried out in a vacuum freeze dryer, the drying time is 2-4 hours, the freeze drying temperature is -20°C to -40°C, and the vacuum pressure is 60-100Pa.

[0022] Further, the oxidized asphalt is coal-tar-based oxidized asphalt or petroleum-tar-based oxidized asphalt;

[0023] The present invention also provides the use of the sodium ion battery hard carbon negative electrode material obtained by the above preparation method in the preparation of sodium ion batteries.

[0024] Compared with the prior art, the technical solution of the present invention has the following advantages and beneficial effects:

[0025] 1. Using agricultural solid waste as raw material for preparing hard carbon negative electrode has wide sources, abundant reserves, low cost and low pollution;

[0026] 2. Adding oxidized asphalt during high-temperature carbonization, the residual carbon after carbonization of the oxidized asphalt is filled into the micropores of the hard carbon negative electrode precursor and coated on its surface, which can reduce the specific surface area of ​​the hard carbon negative electrode, modify the surface by coating, reduce the reversible lithium consumption during the charge and discharge process, and ultimately improve the first efficiency; the prior art adds unoxidized carbon fiber spinning asphalt, which will form a graphite-like structure after carbonization, and the capacity of sodium ions in the graphite structure is not fully utilized, and the first efficiency is low;

[0027] 3. The hard carbon negative electrode precursor after high-temperature carbonization is crushed by a wheel mill. Compared with the mechanical mill used in the prior art, the structural damage to the material is small, the proportion of micro powder of the crushed material is small, the K value of the particle size distribution is small, the particle size distribution is narrow, and the tap density is large; at the same time, a vibrating screen with ultrasonic waves is used, which has a fast screening efficiency and a high yield compared with the simple vibrating screen used in the prior art;

[0028] 4. The carbonized material is incinerated with a boron-containing alkali metal compound and then treated with dilute hydrochloric acid. The boron-containing alkali metal compound can convert the silicate ash in the biomass hard carbon into alkali metal silicate during the incineration process, and then remove it by acidification with dilute hydrochloric acid. In the prior art, concentrated sulfuric acid or aqua regia is usually used to remove ash. Both are strongly acidic substances, and the reaction conditions are severe. The requirements for reaction equipment and operation are high, and the practicality is poor. In addition, the boron element and the carbon element, the main component element of the hard carbon negative electrode, belong to the same period and are in adjacent positions. They have similar chemical properties. When the boron element is doped into the hard carbon lattice in the form of a heteroatom, a defective solid solution is formed, which leads to an increase in its lattice defects, thereby increasing the surface density of the Fermi state, making it electron-rich, and thus improving the conductivity and rate performance of the hard carbon material. Therefore, the addition of a boron-containing alkali metal compound can both reduce the ash content in the hard carbon negative electrode and improve its rate performance.

[0029] 5. The filtrate after washing and filtration is dehydrated using freeze-drying technology. Freeze-drying is the process of freezing the water in the filtrate into a solid state under a vacuum state, and then dehydrating it after sublimation into water vapor. Compared with the constant temperature drying and dehydration technology under normal pressure air atmosphere used in the prior art, the freeze-dried product will not generate chemical bonds with large bond energy such as hydrogen bonds, thereby not producing hard lumps, and no subsequent crushing is required, which simplifies the preparation process and shortens the preparation cycle, while avoiding the damage to the structure of the hard carbon negative electrode material caused by crushing. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1-3 They are the charge and discharge curves of button-type batteries prepared from the negative electrode materials of the comparative example and Examples 1-2 in the test examples.

[0031] Figure 4 2 is a scanning electron microscope photograph of Example 2. DETAILED DESCRIPTION

[0032] The technical solution of the present invention is described below through specific embodiments.

[0033] In the following examples and comparative examples:

[0034] The washing in step (3) is all done with ultrapure deionized water, the ion conductivity of which is controlled at 1-1.5 μΩ / cm, the mass ratio of water to the object to be washed is controlled at 10 / 1-2 / 1, and the washing is performed until the pH of the filtrate is greater than 6;

[0035] The purity of the nitrogen used was 99.5%, and the nitrogen flow rate was 150-200 ml / min.

[0036] Embodiment 1 A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0037] (1) The potato straw was washed, dried, and cut into blocks of 1-2 cm in length. The blocks were crushed in a Chinese herbal medicine crusher and then sieved. The main machine speed during crushing was 12000 r / min, the crushing time was 60 s, and the sieving was carried out in a vibrating screen for 8 minutes. The sieve hole diameter was 300 mesh. The D10 of the sieved material was 4.64 μm, D50 was 12.8 μm, and D90 was 28.45 μm. The particle size distribution coefficient k value, i.e. (D90-D10) / D50, was 1.86.

[0038] (2) The above-obtained undersize material and coal tar-based oxidized asphalt were mixed uniformly at a mass ratio of 100:12, and then carbonized at 850°C for 2 hours in a nitrogen-filled tubular furnace. The obtained carbonized product was treated in a wheel mill for 10 minutes and then sieved using a vibrating screen with ultrasonic waves, wherein the grinding conditions were: 1. spiral speed 12 r / min; 2. grinding time 10 minutes; and the sieving conditions were: ultrasonic intensity: 50%, amplitude: 3 mm, and sieving time 8 minutes;

[0039] (3) The sieve material after sieving in step (2) and borax are mixed in a ratio of 1 / 3, and then incinerated in a muffle furnace at 900° C. for 1.5 hours. 50 ml / L of dilute hydrochloric acid is added to the remaining product, and the volume ratio of the mass of the sieve material to the dilute hydrochloric acid is 10 mg / 150 mL. Then, the mixture is stirred and reacted at 80° C. and a speed of 80 r / min for 4 hours. The obtained reaction product is washed with ultrapure deionized water, filtered, and freeze-dried in a freeze dryer for 2 hours (freeze drying temperature -30° C., freeze drying pressure 80 Pa) to obtain a sodium ion battery hard carbon negative electrode material.

[0040] Embodiment 2 A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0041] (1) Prepare the undersize material in the same manner as step (1) of Example 1.

[0042] (2) The above-obtained undersize and petroleum asphalt-based oxidized asphalt were mixed uniformly in a mass ratio of 100:14, and then carbonized at 900°C for 2 hours in a nitrogen-filled tubular furnace. The obtained carbonized product was treated in a wheel mill for 10 minutes and then sieved using a vibrating screen with ultrasonic waves, wherein the grinding conditions were: 1. spiral speed 20 r / min; 2. grinding time 8 minutes; and the sieving conditions were: ultrasonic intensity: 60%, amplitude: 2 mm, and sieving time 10 minutes;

[0043] (3) The sieve material after screening in step (2) and a sodium carbonate / boric acid mixture (the mass ratio of sodium carbonate to boric acid is 2:8 to 4:6) are mixed uniformly in a mass ratio of 1:4, and then incinerated in a muffle furnace at 900° C. for 1.5 hours. 50 ml / L of dilute hydrochloric acid is added to the remaining product, and the volume ratio of the mass of the sieve material to the dilute hydrochloric acid is 10 mg / 200 mL. Then, the mixture is stirred and reacted at 80° C. and a speed of 80 r / min for 4 hours. The obtained reaction product is washed with ultrapure deionized water, filtered, and freeze-dried in a freeze dryer for 2 hours (freeze drying temperature -30° C., freeze drying pressure 80 Pa) to obtain a sodium ion battery hard carbon negative electrode material.

[0044] Note: The concentration unit of hydrochloric acid, ml / L, is the volume ratio of 37% concentrated hydrochloric acid to water.

[0045] Comparative Example A method for preparing a hard carbon negative electrode material for a sodium ion battery comprises the following steps:

[0046] (1) Same as step (1) of Example 1;

[0047] (2) the above-obtained undersize material and carbon fiber spinning pitch were mixed uniformly in a mass ratio of 100:12, and then carbonized at 850°C in a nitrogen tubular atmosphere furnace for 2 hours. The carbonized product was treated in a mechanical mill for 10 minutes and then sieved with a vibrating screen;

[0048] (3) Add the sieve material of step (2) to 50 ml / L of dilute hydrochloric acid (the volume ratio of the mass of the sieve material to the dilute hydrochloric acid is 10 mg / 200 mL), and then stir and react at a constant temperature of 80° C. and 80 r / min for 4 hours. The reaction product is washed with ultrapure deionized water and filtered, and then dried at a constant temperature of 120° C. in a constant temperature blast drying oven under normal pressure for 4 hours, and then crushed and sieved to obtain a hard carbon negative electrode material for a sodium ion battery.

[0049] Test example:

[0050] The sodium ion battery hard carbon negative electrode materials prepared in Example 1-2 and the comparative example were tested for various physical and chemical indicators (the results are shown in Table 1). Then, MnO2 was used as the positive electrode active material, and the sodium ion battery hard carbon negative electrode materials prepared in the comparative example and step (3) of Example 1-2 were used as negative electrode active materials to assemble CR2430 button batteries for electrical performance testing. The results are shown in Table 2.

[0051] Basic parameter settings for charge and discharge tests:

[0052] 1. First efficiency and gram capacity test: 1. Let stand for 2 hours; 2. 0.1C discharge, cut-off voltage 0.01V; 3. 0.09-0.02C discharge, cut-off voltage 0.005V; 4. Let stand for 15 minutes; 5. 0.1C charge, cut-off voltage 1.5V.

[0053] 2. Rate test: First set the charge and discharge test parameters according to the first effect and gram capacity test parameters for one time, then charge and discharge once at 0.2C, with a cut-off voltage of 0.005V-1.5V and a standing time of 15 minutes; then charge and discharge once at 0.5C, with a cut-off voltage of 0.005-1.5V and a standing time of 15 minutes; then charge and discharge once at 1C, with a cut-off voltage of 0.005-1.5V and a standing time of 15 minutes.

[0054] 3. Cycle performance test: Charge and discharge 100 times according to the rate test parameter settings, that is, 100 times of 1C charge and discharge cycles, cut-off voltage 0.005-1.5V, and stand for 15 minutes.

[0055] Table 1

[0056]

[0057] Table 2

[0058]

[0059] Note: Screening time refers to the time when no more material on the screen is screened off. Specifically in Table 1, it means: after the carbonized product is treated in the wheel mill for 10 minutes, it is screened with a vibrating screen with ultrasonic wave; the mesh size of the screen used is 250 mesh and the diameter of the screen is 30 cm.

[0060] The proportion of micro powder is the mass ratio of the material with a particle size of less than 1 micron in the total amount of the product after wheel grinding;

[0061] The ash content is detected by the weight method, and the specific conditions are: after weighing 1g of negative electrode material sample and heating it at 900° for 2 hours, the mass of the residue is the percentage of the total mass of the weighed material.

[0062] The yield refers to the screening yield when using an ultrasonic vibrating screen or a vibrating screen for screening in step (2).

Claims

1. A method for preparing a hard carbon negative electrode material for a sodium ion battery, comprising the following steps: (1) The agricultural solid waste powder and oxidized asphalt are mixed evenly and then subjected to high-temperature carbonization to obtain a modified product, wherein the amount of the oxidized asphalt accounts for 10%-20% of the mass of the agricultural solid waste powder, and the high-temperature carbonization is carried out in a tubular furnace with protective gas, the carbonization temperature is 800-1000° C., and the carbonization time is 1-5 hours; (2) crushing the modified product obtained in step (1) in a wheel mill, sieving and grading it in an ultrasonic vibration screen, and taking the undersize; (3) The above-mentioned sieve material is mixed evenly with substance A which is a mixture of a boron-containing alkali metal compound or a boron-containing alkali metal compound and an alkali metal compound, and then ashed under protective gas conditions at 900-1000° C. for 1-3 hours to obtain an ashing product, and 50-150 ml / L of dilute hydrochloric acid is added to the ashing product as a modifier for reaction, and then washed, filtered, and dried to obtain the final product, a sodium ion battery hard carbon negative electrode material, wherein the mass ratio of the sieve material to substance A is 1: (2-4).

2. The preparation method according to claim 1, characterized in that: The particle size control conditions of the agricultural solid waste powder in step (1) are as follows: D10=4-6μm, D50=12-14μm, D90<30μm, and particle size distribution K value=1.6-2.

0.

3. The preparation method according to claim 2, characterized in that: The agricultural solid waste powder in step (1) is obtained by washing, drying, cutting, crushing and sieving agricultural solid waste into agricultural solid waste powder. The crushing is carried out in a pulverizer with a main machine speed of 12000 r / min and a crushing time of 30s-60s; the sieving time is 5-10 minutes and the sieve hole diameter is 250-325 mesh.

4. The preparation method according to claim 3, characterized in that: The agricultural solid waste is potato straw, corn straw and / or sunflower straw.

5. The preparation method according to claim 1, characterized in that: The crushing conditions in step (2) are: screw speed 8-25 r / min; grinding time 8-10 minutes; screening conditions are: ultrasonic intensity 20%-80%, amplitude 1-3 mm, screening time 6-10 minutes.

6. The preparation method according to claim 1, characterized in that: The ratio of the sieve material to the dilute hydrochloric acid in step (3) is 1 mg: (10-30) mL.

7. The preparation method according to claim 1, characterized in that: The washing in step (3) is performed with ultrapure deionized water, the ion conductivity of the ultrapure deionized water is controlled at 1-1.5 μΩ / cm, and the pH value of the filtrate is controlled to be greater than 6; the drying in step (3) is performed in a vacuum freeze dryer, the drying time is 2-4 hours, the freeze drying temperature is -20°C to -40°C, and the vacuum pressure is 60-100 Pa.

8. The preparation method according to claim 1, characterized in that: The oxidized asphalt is coal-tar-based oxidized asphalt or petroleum-tar-based oxidized asphalt.

9. Use of the sodium ion battery hard carbon negative electrode material obtained by the preparation method according to any one of claims 1 to 8 in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • Carbon material for sodium-ion battery negative electrode, preparation method of carbon material, sodium-ion battery negative electrode plate and sodium-ion battery

    CN114956037A

  • Hard carbon material applied to sodium ion battery and preparation method of hard carbon material

    CN115991465A